2019
DOI: 10.1016/j.pmedr.2019.100936
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of oral and general health risk behaviors among adolescents

Abstract: Since the co-occurrence of several health-risk behaviors is associated with an increase in chronic diseases, the study of clustering is relevant. The aim of this study was to evaluate how seven types of general and oral health-risk behaviors, cluster among adolescents. A cross-sectional analysis was performed with a sample of high school students from state public schools in São Lourenco da Mata, State of Pernambuco, Brazil (n = 1154). Data were obtained using a self-reported questionnaire. To identify cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…In this study, smoking associated with poor tooth brushing, especially among boys. Earlier studies have shown similar findings among boys and girls [ 18 , 39 ] and among young men [ 40 ]. In general, smokers tend to have poorer oral health habits and oral health than non-smokers have [ 40 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In this study, smoking associated with poor tooth brushing, especially among boys. Earlier studies have shown similar findings among boys and girls [ 18 , 39 ] and among young men [ 40 ]. In general, smokers tend to have poorer oral health habits and oral health than non-smokers have [ 40 ].…”
Section: Discussionsupporting
confidence: 72%
“…One recent study of 71 449 participants found that a higher frequency of daily tooth brushing reduced the development of all types of malignancies [ 41 ]. Additionally, because poor health behaviours tend to cluster together [ 16 , 18 , 39 ], infrequent tooth brushing, together with other poor health habits and other aspects of life, may contribute to poor perceived health.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a survey conducted among adolescents from 9 African countries reported sub-optimal tooth brushing among 22% and only 58% of the sample reported regular handwashing after using the toilet [ 31 ]. Some studies among adolescents have also reported an overlap between behaviors linked to communicable diseases and NCDs [ 32 , 33 ]. This behavioral overlap (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…So far, clustering approaches have been scarcely used to investigate oral conditions. Previous cluster analyses were conducted on oral health attitude and behaviors (Komabayashi et al 2006; Austregésilo et al 2019) and the potential combination of periodontal clinical characteristics and corresponding oral microbial profiles (Boutin et al 2017). To our best knowledge, the NHANES (National Health and Nutrition Examination Survey) is the sole community-based study that correlates clusters of oral health with systemic conditions such as CVD risk factors.…”
Section: Discussionmentioning
confidence: 99%